1967
DOI: 10.1017/s0305004100041475
|View full text |Cite
|
Sign up to set email alerts
|

Stability of an elastico-viscous liquid film flowing down an inclined plane

Abstract: An analysis is made of the stability of a layer of an elastico-viscous liquid flowing down an inclined plane in the presence of two-dimensional disturbances. The modified Orr-Sommerfeld equation is solved by a regular perturbation technique for disturbances of large wavelengths. It is shown that in the absence of surface tension, the layer is more unstable as compared with that for an ordinary viscous liquid if Q1 > Q2, Q1 and Q2 being stress relaxation and strain retardation parameters respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The instability of this film is driven by surface forces, just a5 the droplet breakup is driven by interfacial forces. Also in this case the instability is enhanced by the elasticity of the fluid for both an Oldroyd-B fluid (Lai, 1967;Gupta and Rai, 1967) and a Coleman and No11 second-order fluid (Gupta, 1967;Gupta and Rai, 1968;Minale and Astarita, 1996).…”
Section: Figure 2 Hysteresis Region For Blends Of Pdms In Pi9mentioning
confidence: 89%
“…The instability of this film is driven by surface forces, just a5 the droplet breakup is driven by interfacial forces. Also in this case the instability is enhanced by the elasticity of the fluid for both an Oldroyd-B fluid (Lai, 1967;Gupta and Rai, 1967) and a Coleman and No11 second-order fluid (Gupta, 1967;Gupta and Rai, 1968;Minale and Astarita, 1996).…”
Section: Figure 2 Hysteresis Region For Blends Of Pdms In Pi9mentioning
confidence: 89%
“…a Deborah number, De, should satisfy De ⌧ 1) and are best-suited for steady or quasi-steady ('slow') flows [10]. The Oldroyd-B constitutive model is better-suited for unsteady shear flows with substantial viscoelastic e↵ects, and subsequent linear stability studies using this model (or the closely-related Upper-convected Maxwell model) confirmed the destabilizing influence of viscoelasticity and also revealed that an elastic instability may be present if the Deborah number is su ciently large (even when the Reynolds number is zero) [11][12][13][14][15]. Viscoelastic analogues to the Benney [16][17][18] and IBL [19] equations have also been derived and analyzed, and numerical simulations of both the Newtonian and viscoelastic Benney equations indicate that a variety of nonlinear states including travelling waves and chaos may be excited (see [20] and section V).…”
Section: Introductionmentioning
confidence: 93%
“…For instance, the constitutive equation for Oldroyd's 'liquid B ' (see Oldroyd 1950) is found to yield only stable solutions to the same problem. I n fact, this constitutive equation has been adopted by Wei Lai (1967) and by Gupta & Rai (1967) to examine the stability of flow down an inclined plane.…”
Section: -51mentioning
confidence: 99%